ANALISIS PENGARUH PROFESIONALISME PEMERIKSA PAJAK, KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA FISKUS DENGAN AUDIT JUDGMENT SEBAGAI VARIABEL INTERVENING (Studi Pada Kantor Pelayanan Pajak Di Wilayah Jakarta Timur) - Sri Widari (TEKUN: Jurnal Telaah Akuntansi dan Bisnis, 2017)
The primary data in this study was obtained from the questionnaire answers to tax inspectors Tax Office Region East Jakarta. The data can be collected as many as 107 people from 140 questionnaires distributed to the tax inspectors. This is due to a mutation on a large scale at Regional Tax Office, East Jakarta. Statistical methods were used to test each hypothesis is SEM analysis on the program Lisrel The results of this study indicate that not all hypotheses are built to be accepted, it demonstrates that positively affect the professionalism and commitment of audit judgment, but this study did not find evidence of professionalism influence on job satisfaction and organizational commitment, this happens probably because the value of professionalism adopted tax inspectors often conflict with rules that differ from the environment in which auditors work